Respuesta :
-3x + y - 2z = 10 |* -1
3x - y +2z = -10
5x -2y -2z = 12
--------------------------- I add these equations term by term
8x - 3y = 2
-3x + y - 2z =10 ⇒ -3x + y - 2z =10
x -y +z = 23 | *2 2x - 2y + 2z = 46
----------------------------- I add these eq.
-x -y = 56
8x - 3y = 2
-x -y = 56
this is the system after i reduce it ( it has only two variables x and y)
3x - y +2z = -10
5x -2y -2z = 12
--------------------------- I add these equations term by term
8x - 3y = 2
-3x + y - 2z =10 ⇒ -3x + y - 2z =10
x -y +z = 23 | *2 2x - 2y + 2z = 46
----------------------------- I add these eq.
-x -y = 56
8x - 3y = 2
-x -y = 56
this is the system after i reduce it ( it has only two variables x and y)
Answer:
Eliminate y by adding equations (1) and (3) because the coefficients on y are opposites. Then eliminate y by multiplying equation (1) by 2 and adding it to equation (2).
Eliminate z by subtracting equations (1) and (2) because the coefficients are the same. Then eliminate z by multiplying equation (3) by 2 and adding it to equation (1).
Step-by-step explanation:
The variables have to be the same in both equations in the 2 × 2 system.
All of this should be included